2003
DOI: 10.1182/blood-2002-10-3188
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of tissue factor pathway inhibitor (TFPI) increase the risk of venous thrombosis

Abstract: There is now strong experimental evidence that tissue factor pathway inhibitor (TFPI) is a critical inhibitor to modulate tissue factor-induced coagulation, but the role of TFPI as a risk factor for thrombosis is yet to be to be determined. This study investigated the role of low TFPI levels for the development of deep-vein thrombosis (DVT). We determined TFPI activity and TFPI-free and total antigen levels in the subjects enrolled in the Leiden Thrombophilia Study, which is a large population-based case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
208
4
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(225 citation statements)
references
References 44 publications
(41 reference statements)
10
208
4
3
Order By: Relevance
“…Mean f-TFPI and sTM did not differ significantly between cases and controls irrespective of the type of event. Because it was recently shown that f-TFPI levels below the 10th percentile were a risk factor for venous thrombosis, 17 supporting a threshold effect, we performed a similar analysis in the present study. Of the individuals with hard CHD, 13.3% presented values below the cutoff, compared with 8.3% of the controls (Pϭ0.07).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Mean f-TFPI and sTM did not differ significantly between cases and controls irrespective of the type of event. Because it was recently shown that f-TFPI levels below the 10th percentile were a risk factor for venous thrombosis, 17 supporting a threshold effect, we performed a similar analysis in the present study. Of the individuals with hard CHD, 13.3% presented values below the cutoff, compared with 8.3% of the controls (Pϭ0.07).…”
Section: Resultsmentioning
confidence: 91%
“…Quartiles were used for vWF, f-TFPI, and sTM, whereas f-TFPI was also categorized according to the 10th percentile of the distribution in controls, as previously suggested. 17 A conditional regression analysis suitable for a nested case-control design was performed to identify discriminating predictive parameters. The same analysis was used to determine the relative risk of future CHD events after control for different sets of variables: (1) body mass index (BMI), total cholesterol, HDL cholesterol, systolic blood pressure, smoking, alcohol, and diabetes; (2) further adjustment for CRP, TNF-␣, IL-6, and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It has been demonstrated that short-term PM exposure significantly decreased plasma TFPI level. 51 Decreased circulating TFPI levels have been linked to venous thrombosis 52 ; however, lung TFPI expression and regulation by Sirt1 after PM exposure have not been investigated. In this study, we demonstrated that lung TFPI expression was decreased after PM exposure, and Sirt1 deletion resulted in further reduction of TFPI levels in the lung, suggesting that Sirt1 could control coagulation responses by regulating TFPI expression.…”
Section: Sirt1 Controls Lung Inflammation and Coagulation 2427mentioning
confidence: 99%
“…1 It circulates in plasma at a concentration of ;1.6 nM. 2,3 The majority (;80%) of plasma TFPI is truncated and bound to lipoproteins, ;5% is localized in storage granules within platelets, ;5% circulates as free truncated variants, and only around 10% is considered to be free full-length TFPI, 4 with this having the greatest anticoagulant activity. [5][6][7] TFPI and its cofactor protein S downregulate tissue factor (TF)-induced thrombin generation, and a deficiency of either protein has been linked to an increased risk of venous thrombosis.…”
Section: Introductionmentioning
confidence: 99%